Effeectivenss of Reminiscence Therapy on Depression Level Among Elderly - Lia Juniarni; linlin lindayani; Gina Nurdina; Agus Hendra (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The elderly suffer from one or more chronic diseases or disabilities and as they age, their prevalence increases. One of the most common aging problems more commonly found in nursing homes is depression. Currently increasing research and reviews support the efficiency of psychotherapy treatments for depression. Based on traditional interventions, reminiscence therapy is recommended for geriatric depression. Reminiscence therapy focuses on accepting one's past life, viewing one's past life as a valuable and satisfying period, finding meaning in life, narrowing the gap between reality and dreams, accepting negative past events and recognizing ongoing patterns between the past and present. The purpose of evidence-based practice is to determine the effectiveness of reminiscence therapy on the level of depression in the elderly. Literature searches conducted through Google Scholar and Pubmed using combination of keyword reminiscence therapy, depression, elderly. Inclusion criteria were studies published in English from 2010 to 2020. There were 535 journals obtained, but only 5 journals met the search criteria. The results of this review indicate that reminiscence therapy has an influence to reduce the level of depression in lanisa and reminiscence therapy has no side effects compared to pharmacological therapy. It is expected that health workers can implement reminiscence therapy to reduce the level of depression in the elderly.